Pengaruh Self Efficacy, Komitmen dan Disiplin Kerja Terhadap Kinerja Pegawai Kelurahan di Kecamatan Lowokwaru - Siti Mufidatun Kasanah; Budi Wahono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Human resources are needed for the development of an institution, occupy an important position. For determining the success of an institution, it needs to pay attention to its employee performance. To find out the findings, this study was conducted to know the effect of self efficacy, commitment and work discipline on the village official’s performance in Lowokwaru District. The research design was quantitative research that had a population with a total sample of 51 employees in the sub-district of Lowokwaru District that was drawn by using the slovin formula. Meanwhile, for analyzing the data, this research used multiple linear regression technique. From the research, it showed that this study indicated the variabels of self efficacy, commitment and work discipline that affect positively to the employee performance partially. Therefore, it can be concluded that the higher the self efficacy, commitment and work discipline, the better the employees will be in improving their performance. Keywords: Employee Performance, Self Efficacy, Commitment and Work Discipline